Multi-objective Optimization Design of Moving Mechanism Configuration for Two-wheel Differential Driving Service Robot - Zhang Xiaoli; Liang Dong; Shan Xinping; Chen Bingkui (Jixie chuandong)
The moving mechanism configuration has a major impact on the static stability,dynamic stability and driving force of the wheeled service robot. Taking the six-wheel mobile underpan as the object,the relationships between the wheel layout and the static stability,dynamic stability,driving force to cross obstacle and turn are analyzed. A multi-objective optimization model for wheel layout is established and the optimal solution is derived by using MATLAB genetic algorithm toolbox. Assuming the factors of pitch angle,roll angle and drive torque as evaluation indicators,motion simulation of the mobile underpan is carried out by the virtual prototyping technology. The results show that the pitch angle and roll angle after optimization are decreased by17. 6% and 27. 2%,respectively. The average value and mean square of drive torque are decreased by 2. 8%and 3. 6%,respectively. It is beneficial to the transmission performance and endurance of the mobile underpan. The results also verify the correctness and validity of the established multi-objective optimization model.